Cognitive Attributes, Attention, and Self‐Efficacy of Adequate and Inadequate Responders in a Fourth Grade Reading Intervention. Issue 4 (28th October 2015) - Cho, Eunsoo; Roberts, Garrett J.; Capin, Philip; Roberts, Greg; Miciak, Jeremy; Vaughn, Sharon
Abstract : We examined cognitive attributes, attention, and self‐efficacy of fourth grade struggling readers who were identified as adequate responders ( n = 27), inadequate responders with comprehension only deficits ( n = 46), and inadequate responders with comprehension and word reading deficits ( n = 52) after receiving a multicomponent reading intervention. We also included typical readers ( n = 40). These four groups were compared on measures of nonverbal reasoning, working memory, verbal knowledge, listening comprehension, phonological awareness, and rapid naming as well as on teacher ratings of attention problems and self‐reported self‐efficacy. The two inadequate responder groups demonstrated difficulties primarily with verbal knowledge and listening comprehension compared to typical readers and adequate responders. Phonological awareness and rapid naming differentiated the two inadequate responder groups. In addition, both inadequate responder groups showed more attention problems and low self‐efficacy compared to typical readers.